STRATEGI POLITIK AKAR RUMPUT DALAM PEMENANGAN HALIANA-ILMIATI PADA PEMILIHAN SERENTAK 2020: (Studi di Kecamatan Wangi-Wangi Selatan Kabupaten Wakatobi) - Amirudin; Muh. Zein Abdullah; Risman (Journal Publicuho, 2023)
The purpose of this study was to find out the grassroots political strategy in winning Haliana-Ilmiati in the 2020 Simultaneous elections in Wakatobi Regency. The research method used in this research is descriptive qualitative. Data collection techniques using interviews and documentation. Data analysis techniques using qualitative interactive data analysis techniques by reducing data, presenting data and drawing conclusions. The results showed that the winning strategy for the elected regent and deputy regent pairs in the 2020 regional head election in Wakatobi district, the winning team had implemented a grassroots political strategy, where the Haliana-Ilmiati pair hooked up all groups in society, starting from the community leaders, young people and also among mothers. The grassroots political strategy uses 1) segmentation, in which the Haliana-Ilmiati winning team groups voters based on region and age, this is reflected in the vision and mission of the Haliana-Ilmiati pair. 2) Targeted, where the target of the winning team are community leaders, young people and mothers. 3) positioning, where the Haliana-Ilmiati winning team made visits directly to the community to obtain aspirations and find out the needs of the community in Wakatobi.